THE EFFECT OF RETURN ON EQUITY AND GROWTH ASSETS ON PRICE BOOK VALUE WITH DEBT TO EQUITY AS AN INTERVENING VARIABLE IN REGISTERED METAL SUB-SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE - Afrita Nasution, Yusneni; Muslim, Muslim; Afdillah, Soraya (RADJA PUBLIKA, 2021)
This study aims to determine the effect of Return On Equity, Change In Total Assets on Price Book Value with Debt To Equity as an intervening in metal sub-sector companies listed on the Indonesia Stock Exchange. This study is an associative study with documentation data collection techniques, the population in this study This amounted to 16 companies and samples taken amounted to 14 companies. The sampling technique used is purposive sampling technique. The analytical method used is path analysis. The results showed that Return On Equity had a positive and significant effect on Debt To Equity, Return On Equity had a positive and insignificant effect on Price Book Value, Growth Assets had a positive and insignificant effect on Debt To Equity, Growth Assets had a positive and insignificant effect on Price Book Value, Debt to Equity has a positive and insignificant effect on Price Book Value, Debt to Equity as a mediation on Return On Equity and Price Book Value has a negative and insignificant effect, Debt to Equity as a mediation on Growth Assets and Price Book Value has a negative and negative effect not significant.